A CASE SERIES OF VARICOSITIES LINGUALIS WITH HYPERTENSION AS A PREDISPOSING FACTOR - Megawati, Ani; Sekarini, Nabela Intania; Rohmah, Mufidatul; Hasanah, Anies Sayla (Universitas Muhammadiyah Semarang, 2024)
Background: Varicosities lingualis were enlarged veins that are prominent and visible on the ventral surface of the tongue. The etiology of varicosities is physiological aging and predisposing factors including hypertension, obesity, smoking, and diabetes mellitus. This serial case aims to assess the relationship between varicosities lingualis and hypertension as a predisposing factor.Method: The case report method uses three patient subjects who write using the SOAP method (Subjective, Objective, Assessment, and Planning).Outcome: Three patients, one female and two males with an age range of 19 years to 25 years, complained of a purplish-blue line under the tongue. All cases showed a purplish-blue line under the tongue. The management given is non-pharmacological, including Communication, Information, and Education (IEC).Conclusion: Hypertension plays an essential role as a predisposing factor in the development of varicosities lingualis due to the hemodynamic effects that cause dilation of blood vessels.